Management of Islamic-Based Character Education Implementation in Vocational Schools - Hamid, Eka Abdul; Bahari, M. Farid Yudha; Hernawati (LETIGES, 2025)
This study investigates the management of Islamic-based character education implementation in vocational schools in Indonesia, focusing on how moral values are systematically integrated into school governance. The research employs a qualitative case study approach at SMKN 1 Buahdua, with data collected through in-depth interviews, classroom observations, and document analysis. The participants included school leaders, Islamic Education teachers, and general subject teachers. Data were analysed using Miles and Huberman's interactive model, which involves data condensation, data display, and conclusion drawing. Findings indicate that school leadership is central yet underutilised in formulating institutional strategies for character education. Despite teachers' efforts, especially from the Islamic Education department, there is a lack of institutional planning documents, such as formal guidelines, performance indicators, or curriculum integration strategies. Leadership fails to transform fragmented teacher initiatives into a coherent management plan. Character education remains unstructured, as general subject teachers receive no formal training, guidance, or coordinated support. Furthermore, challenges in implementation arise from the absence of interdepartmental coordination, inadequate professional development, and unclear conceptualisation of moral goals. Evaluation mechanisms are informal and lack standardised tools, while family and community involvement is minimal, weakening long-term value formation. These findings reflect a managerial deficit in planning, organising, actuating, and controlling (POAC) Islamic character education within vocational settings. To address these issues, the study proposes a management-oriented model encompassing strategic planning, cross-departmental collaboration, structured training, stakeholder engagement, and the development of formative character assessment instruments based on Islamic ethics. This model seeks to institutionalise character education not as a supplementary effort but as a core component of educational management that aligns moral development with vocational excellence.